Negotiating "meaningful participation" for Indigenous peoples in the context of mining. Issue 4 (1st August 2016) - Ruwhiu, Diane; Carter, Lynette
Abstract : Purpose: This paper aims to explore the importance of meaningful participation for Indigenous peoples within the complex and highly political context of mining and mineral extraction. The aim is to consider the multi-dimensional nature of the mining context that takes into account the discursive landscape that frames the often disparate perspectives of corporate, state and Indigenous communities. Design/methodology/approach: The paper is a conceptual offering that examines the complex environment within which "meaningful participation" between mining corporates and Indigenous communities operate. Findings: This paper highlights the multi-dimensional nature of a proposed relationship between the mining corporates, the state and the Indigenous Māori community within New Zealand. The facilitation of "meaningful participation" requires that any negotiated agreement is undertaken within a framework of meaning that makes sense to the Indigenous community, in addition to the appropriate legislative and corporate initiatives to be in place. Originality/value: The paper highlights the complex considerations that must be included in any form of negotiation between mining corporates and Indigenous peoples to achieve meaningful participation in the form that it was intended under international accords. While recognising the different contextual circumstance of Indigenous peoples around the world, this paper illustrates a pathway towards meaningful participation that takes into account economic, socio-cultural and environmental variables.